What Makes Us Move, What Makes Us Stay: The Role of Language and Culture in Intra-EU Mobility - Ekaterina Sprenger (Journal of International Migration and Integration, 2024)
This article analyses the determinants of international migration flows within the European Union and specifically focuses on the role of cultural and linguistic differences in explaining the size of these flows. For that purpose, a set of indicators of cultural distance is controlled for along with economic, demographic, geographical, political and network variables using data from 28 member states of the EU over the period 1998–2018. Economic factors play an important role in examining migration flows, but economic differentials alone may be insufficient to explain the uneven real-life migration pattern in the EU. The results suggest strong evidence of the importance of linguistic distance in explaining the direction of migration flows across the EU.
Keywords: J61; F22; O15; 300; European Union; Geographic mobility; Labour mobility; Migration; Optimum currency area